The impact of sports preferences on physical activity participation among college students: the mediating role of sports achievement emotions and exercise motivation - Sun, Yi; Zhao, Yang; Yang, Jie (Frontiers in Psychology, 2025)
BackgroundCollege students commonly exhibit low levels of physical activity participation, which not only impacts physical health but also negatively affects mental well-being and academic performance. Although existing research has focused on the effects of sports preference, sports achievement emotions, and exercise motivation on physical activity participation, the interactive mechanisms among these three factors have yet to be systematically explored.ObjectiveThis study aims to investigate how college students’ sports preferences, sports achievement emotions, and exercise motivation influence physical activity participation through mediating effects.MethodsA cross-sectional questionnaire survey was conducted online, recruiting 801 undergraduates (58.18% female). The study utilized a sports preference scale, a sports achievement emotion questionnaire, an exercise motivation scale, and the number of days per week of moderate-to-vigorous physical activity to measure the variables. After controlling for demographic characteristics, mediation effect analysis was performed using Stata 17.0.ResultsSports preferences (SP) had a significant positive direct effect on physical activity participation (PAP) among college students (B = 55.494, p < 0.001). Positive sports achievement emotions (PSAE) significantly mediated the relationship between SP and PAP (indirect effect = 5.644, p < 0.001). Exercise motivation (EM) also exhibited a significant mediating effect (indirect effect = 2.304, p < 0.001). Moreover, a positive correlation between PSAE and EM was observed, creating a chain mediation effect (SP → PSAE → EM → PAP), with an indirect effect of 1.424 (p < 0.001). These findings suggest that sports preferences not only directly enhance physical activity levels but also promote physical activity participation through a multi-level pathway involving positive emotions and exercise motivation.ConclusionCollege students’ sports preferences significantly predict physical activity participation, with positive sports achievement emotions and exercise motivation playing crucial roles as mediators and chain mediators. Future research should incorporate longitudinal designs or intervention experiments and include more diverse evaluation indicators to further validate and extend the findings of this study.